A fast search strategy to optimise path founding in big data graph computing environments. (2017) - Qu, Wentian; Sun, Dawei
In big data graph computing environments, the shortest path problem is very important and widely applied in various scenarios. But sometimes, in order to find the shortest path, it always entails a lot of cost. So, weighing the various aspects of the problems, it's a good choice to find optimal path. In this paper, an improved A-star algorithm is proposed to define the optimal path. A-star algorithm has two kinds of parameters named actual cost and estimated cost and the second one plays an important part in the algorithm. Based on the traditional A-star algorithm, this paper will propose new parameters and improved heuristic function to enhance the performance of the A-star algorithm. Compared with the traditional A-star algorithm, the simulation experiment shows that the improved A-star algorithm runs at high efficiency. Two factors which affect the best situation are also discussed in the end of this paper.